Discursive devices for inserting morality into law: initial exploration from the analysis of a Brazilian Supreme Court decision - Pádua, João Pedro (2019)
The dierences and intersections between law and morality are a pervasive theme in legal theory. Scholars have debated for more than a century about how best to distinguish the two as normative phenomena. However, little attention has been paid to how those two normative systems interact with each other on an empirical, i.e., practical level, and to the consequences of this interaction for the theoretical debate that stands above it. Drawing on tools and concepts from discourse analysis – specifically the ethnomethodology of written texts and studies of moral work – this paper aims to attend to the issue of how morality is inserted into legal phenomena by the practical discursive work of jurists. The data comes from a decision by the Brazilian Supreme Court to remove the president of the Lower House of Congress from office following criminal charges. The analysis demonstrates that the judge mixes references to the legal/technical framework with moral work in constructing a deviant character for the defendant. This defendant so-categorized feeds back into legal categories to justify the decision to remove him from office. Implications for the conjoining of morality and law as a practical matter is discussed.